Impact of meteorological conditions on abdominal aortic aneurysm rupture: evaluation of an 18-year period and review of the literature - Schuld, Jochen; Kollmar, Otto; Schuld, Simone; Schommer, Kai; Richter, Sven (Vascular and endovascular surgery, 2013)
Objective: To examine the influence of local meteorological conditions on the onset of ruptured abdominal aortic aneurysms (AAA). Methods: A review of 6551 consecutive days with a total of 191 ruptured AAA was performed between January, 1994 and December, 2011. Days with and without ruptured AAA were compared considering local meteorological data. A systematic review of the literature was performed. Results: Atmospheric pressure, cloudiness, relative humidity, precipitation, and water vapor pressure were comparable at event and nonevent days. The 4-day variance of atmospheric pressure prior to event days was significantly higher compared to nonevent days. Maximal and average temperature and water vapor pressure were significant lower at event days. Binary regression analysis identified a higher 4-day variance in atmospheric pressure as an independent factor for ruptures. Conclusions: Further studies, collected at different geographic and climate areas, are necessary to prove that meteorological conditions may trigger the incidence of ruptured AAA.
Gesehen am 22.07.2021